Adjusting the Structure and Electronic Properties of Carbons for Metal‐Free Carbocatalysis of Organic Transformations. Issue 13 (18th December 2018) - Antonietti, Markus; Lopez‐Salas, Nieves; Primo, Ana
Abstract: Carbon nanomaterials doped with some other lightweight elements were recently described as powerful, heterogeneous, metal‐free organocatalysts, adding to their high performance in electrocatalysis. Here, recent observations in traditional catalysis are reviewed, and the underlying reaction mechanisms of the catalyzed organic transformations are explored. In some cases, these are due to specific active functional sites, but more generally the catalytic activity relates to collective properties of the conjugated nanocarbon frameworks and the electron transfer from and to the catalytic centers and substrates. It is shown that the learnings are tightly related to those of electrocatalysis; i.e., the search for better electrocatalysts also improves chemocatalysis, and vice versa. Carbon–carbon heterojunction effects and some perspectives on future possibilities are discussed at the end. Abstract : Carbon nanomaterials are not only excellent electrocatalysts but also powerful heterogeneous organocatalysts extending the spectrum of metal‐based catalysis. The sometimes‐forgotten history of these observations is first described, followed by highlights of the actual literature with respect to very diverse reaction classes. A personal outlook on potentialities and opportunities is given to close.